Article Evaluation Assignment - Holster, Kristin (TRAILS: Teaching Resources and Innovations Library for Sociology, 2016)
Encouraging students to read sociology articles is a goal of many sociology courses. However, these articles are frequently intimidating for students and they often have a difficult time knowing where in the article to find specific information. This assignment takes students through a step by step process to learn how to locate specific elements of sociology articles. In addition, this assignment encourages students to explore the various goals of sociological research and writing by requiring them to distinguish between basic, public, and applied sociology focusing on the questions "knowledge for what"? and "knowledge for whom"?